E-Learning Platforms in Multilingual Education: A Comprehensive Review of Cloud-Based Solutions for Language Instruction - Moch Yasin; Aram Hakobyan; Michael Jordan (Yayasan Adra Karima Hubbi, 2026)
Background. The increasing demand for multilingual education has prompted the exploration of digital platforms that can support language instruction in diverse linguistic contexts. Cloud-based e-learning platforms have emerged as an effective tool for enhancing language learning, offering scalable, accessible, and interactive environments for students and educators alike. Despite their growing use, a comprehensive analysis of the benefits, challenges, and implementation strategies for cloud-based language education platforms remains limited. Purpose. This study aims to provide a comprehensive review of cloud-based e-learning platforms in the context of multilingual education. The focus is to identify key features, challenges, and best practices for using these platforms to facilitate language instruction in multilingual settings. Method. A systematic review of literature was conducted, synthesizing data from peer-reviewed journals, conference proceedings, and reports from 2015 to 2025. The review evaluated various e-learning platforms based on criteria such as user engagement, accessibility, multilingual support, and pedagogical effectiveness. Results. The findings indicate that cloud-based e-learning platforms provide flexible, customizable solutions that foster collaborative learning in multilingual classrooms. However, challenges such as technological limitations, content localization, and teacher training need to be addressed for effective implementation. Conclusion. Cloud-based e-learning platforms offer significant potential for multilingual language instruction but require targeted strategies for overcoming implementation barriers.